Módulo portátil para pruebas de plc en la universidad Antonio Nariño sede Cúcuta - Martinez Sanguino, Jeisson Oscar (Universidad Antonio Nariño, 2021)
The present degree work aims to design a didactic module for PLC tests aimed at students of the Antonio Nariño University. It will be based on the modern automated control of companies in the industrial sector, in view of the development of the Fourth Industrial Revolution, a time in which modernization at the business level has undermined the factory branch. It will be focused on the methodological design of Scientific Research, using inductive-deductive, experimental, and observational methods, for which they were divided into three stages: design, construction and commissioning, all focused on the realization and achievement of the specific objectives. The results that are expected to be achieved is the construction of a team in the form of a portable module that handles the Ladder programming language, which will be implemented so that the students of the Antonio Nariño University, Cúcuta campus can use it as a learning tool in the electromechanical career.